The Tensions On The Protection Of Local-Traditional Indonesian Batik - Ria Setyawati; Mas Rahmah; Rahmi Jened; Nurul Barizah; Agung Sujatmiko (Universitas Airlangga, 2021)
Batik artwork has been known for hundreds of years and has become part of the culture of Indonesian society. Some batik motifs in Indonesia have philosophical values and are part of traditional traditional ceremony activities. Along with the times, the creativity of batik artists has become varied even though ancient traditional motifs are still mass produced and used as inspiration. This research examines the legal protection for traditional batik in order to avoid the abuse of rights by certain parties who merely exploit it in order to benefit from the existence of traditional batik works. The formulation of the problem that will be examined in this research is whether traditional batik gets legal protection under the copyright regime in Indonesia? Are there any legal safeguards at the international level for traditional Indonesian batik works? In answering this problem formulation will use a conceptual approach and a statutory approach. This research is a legal research that will examine existing legal concepts and related legal rules in solving legal problems related to the protection of traditional batik.